Pengaruh Modal, Lama Usaha Dan Jam Kerja Terhadap Pendapatan Pedagang Di Masjid Tiban Malang - Aminulloh, Mohammad Faris; Salim, Muhammad Agus; Priyono, Achmad Agus (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Economic growth and development is one of the indicators for assessing economic development in a country. Especially in the informal sector, Islamic boarding schools, which in fact are traditional Islamic educational institutions that study, understand, appreciate and practice Islamic teachings, are now not inclined towards this, for example, the Tiban mosque. Now people view the Tiban Mosque as a tourist attraction and no longer as a place that is considered sacred for followers of the Islamic religion. Tiban Mosque is a tourist spot that is visited by many local and foreign residents. The large number of tourists visiting provides an opportunity for business people or traders to sell merchandise in the Tiban Mosque area as a source of income. The aim of this research is to determine and analyze the influence of capital, length of business and working hours simultaneously on the income of the Tiban Malang Mosque traders. and Researchers use quantitative research. Researchers depart from theoretical paradigms towards data, and end in acceptance or rejection of the theory used. Meanwhile, qualitative data is presented in descriptive form to support quantitative data. The research results state that capital, length of business and working hours simultaneously influence traders' income. Keywords: Capital, Length of business, Working hours, Trader's income